Participation and Consequences of Education of Scheduled Castes in Andhra Pradesh - Reddy, P. Adinarayana; Reddy, E. Mahadeva (JOURNAL OF INDIAN EDUCATION, 2009)
The NCERT has designed a multi-centric study covering a number of states to identify the participation and consequences of education of the Scheduled Castes by inviting selected experts in the field. The study was designed to cover selected states and one of the states selected for the study is Andhra Pradesh. The present paper is a part of the project deals mainly with the SC parents’ perceptions towards education of their children, progress of the literacy among Scheduled Castes in the selected districts. The findings of the study includes progress of education of the Scheduled Castes and non-Scheduled Castes in the study area in terms of enrolment, retention, transition, parental perception towards experiences provided by the schools, its accessibility, teacher efficiency etc. Further, it also identifies the progress of literacy in the sample area, the literacy programmes that have been implemented, extent of registrations in the employment exchanges by the Scheduled Castes and non Scheduled Castes in the selected areas were also identified.